Temperature dependence of cycloheximide-sensitive phase of circadian cycle in Acetabularia mediterranea. - Karakashian, M W (1976)
The biochemical nature of the circadian regulatory system that controls many cellular activities is still unclear. Recent results obtained from the application of protein synthesis inhibitors to individual Acetabularia cells expressing circadian rhythms of photosynthesis indicate that some protein(s) must be synthesized on 80S ribosomes during a discrete part of each cycle to insure correct time-keeping. A comparative study of the effects of brief cycloheximide treatments on cells investigated at different temperature has revealed that the phase of cycloheximide sensitivity is 4-6 hr longer and occurs about 8 hr later in the cycle when cells are kept at 20 degrees rather than 25 degrees. Temperature is known to influence the function of the circadian regulatory system in Acetabularia, but the effect on frequency is small (Q10 approximately equal to 0.8) due to the existence of a temperature-compensating feature. The large effects of temperature observed here thus favor the interpretation that protein synthesis on 80S ribosomes, while providing an essential component of the circadian timing mechanism, does not itself generate the period of the photosynthesis rhythm.